Synthesis of 2‐(2‐oxo‐2 H ‐chromen‐4‐yl)acetamides as potent acetylcholinesterase inhibitors and molecular insights into binding interactions - Kara, Jiraporn; Suwanhom, Paptawan; Wattanapiromsakul, Chatchai; Nualnoi, Teerapat; Puripattanavong, Jindaporn; Khongkow, Pasarat; Lee, Vannajan Sanghiran; Gaurav, Anand; Lomlim, Luelak (Wiley-VCH Verlag, 2019)
Sixteen novel coumarin-based compounds are reported as potent acetylcholinesterase (AChE) inhibitors. The most active compound in this series, 5a (IC50 0.04 ± 0.01 µM), noncompetitively inhibited AChE with a higher potency than tacrine and galantamine. Compounds 5d, 5j, and 5 m showed a moderate antilipid peroxidation activity. The compounds showed cytotoxicity in the same range as the standard drugs in HEK-293 cells. Molecular docking demonstrated that 5a acted as a dual binding site inhibitor. The coumarin moiety occupied the peripheral anionic site and showed π-π interaction with Trp278. The tertiary amino group displayed significant cation-π interaction with Phe329. The aromatic group showed π-π interaction with Trp83 at the catalytic anionic site. The long chain of methylene lay along the gorge interacting with Phe330 via hydrophobic interaction. Molecular docking was applied to postulate the selectivity toward AChE of 5a in comparison with donepezil and tacrine. Structural insights into the selectivity of the coumarin derivatives toward huAChE were explored by molecular docking and 3D QSAR and molecular dynamics simulation for 20 ns. ADMET analysis suggested that the 2-(2-oxo-2H-chromen-4-yl)acetamides showed a good pharmacokinetic profile and no hepatotoxicity. These coumarin derivatives showed high potential for further development as anti-Alzheimer agents. © 2019 Deutsche Pharmazeutische Gesellschaft